Foreign trade in goods of Ukraine with EU countries: value dimension - Totska , Olesia (National Interest, 2023)
Ukraine is trying to become a full member of the EU. In 2022, it received the status of a candidate for joining the EU. Ukraine's foreign trade with EU countries takes a significant share in its total foreign trade: in 2021, exports of goods from Ukraine to EU amounted to USD 26,792,969.3 thsd. or 39.36% of the total export of Ukrainian goods; the import of goods from the EU to Ukraine amounted to USD 28,954,281.2 thsd. or 39.75% of the total amount of goods imported to Ukraine. However, the war in Ukraine made adjustments to trade in goods between Ukraine and the EU. The purpose of the article is to analyze the value indicators of Ukraine's foreign trade in goods with EU in 2021 and to determine the impact of the war on Ukraine's export and import operations with the EU in 2022. At the first stage of the study, an ABC analysis of EU countries was carried out separately according to the indicators of export of goods from Ukraine and import of goods to Ukraine. At the second stage of the study, a structural analysis of export/import indicators was carried out for those eight countries that in both cases fell into group A (Poland, Italy, Germany, the Netherlands, Spain, Hungary, the Czech Republic, Slovakia) in order to determine the goods with the largest export/import potential in 2021. At the third stage of the study, the indicators of export/import of goods between Ukraine and the EU for 2022 were analyzed.